PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP LOYALITAS KONSUMEN JASA KAMAR PADA TJOKRO HOTEL PEKANBARU - Siagian, Joko Hendro; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conduced at Tjokro Hotel Pekanbaru located at Jenderal Sudirman Street No. 51 Pekanbaru. The purpose of this study was determine the effect of service quality and pricing on consumer loyalty room service at Tjokro Hotel Pekanbaru partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS Program. The sample of this study was taken as many as 100 respondents from the entire population and calculated using the Slovin formula, a non-probability sampling technique with an accidental sampling technique. Data Collection techniques through interviews and questionnaries, types and source of data using primary data and secondary data, measurement techniques using a Likert Scale.From the analysis of data which includes validity, reliability, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and F test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, service quality on consumer loyalty is t arithmetic (12,442) > t table (1,6605) means that service quality has a significant effect on consumer loyalty . second, price pricing on consumer loyalty is t arithmetic (15,091) > t table (1,6605) means that pricing has a significant effect on concumer loyalty. F Test Results of service quality have a significant effect on consumer loyalty, namely F arithmetic (122.846) > F tables (3,09). This means that service quality and pricing simultaneously have a significant effect on consumer loyalty at Tjokro Hotel Pekanbaru.  Keywords : Service Quality, Pricing, Consumer Loyalty